2012
DOI: 10.1152/ajpheart.00117.2012
|View full text |Cite
|
Sign up to set email alerts
|

A model of preeclampsia in rats: the reduced uterine perfusion pressure (RUPP) model

Abstract: Preeclampsia is defined as new-onset hypertension with proteinuria after 20 wk gestation and is hypothesized to be due to shallow trophoblast invasion in the spiral arteries thus resulting in progressive placental ischemia as the fetus grows. Many animal models have been developed that mimic changes in maternal circulation or immune function associated with preeclampsia. The model of reduced uterine perfusion pressure in pregnant rats closely mimics the hypertension, immune system abnormalities, systemic and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
147
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 173 publications
(158 citation statements)
references
References 103 publications
5
147
2
4
Order By: Relevance
“…Previous work has shown that oxidative stress plays an important role in preeclampsia and RUPP hypertension (25,31), and our present observations suggest that the effects of AICAR may be mediated by a combination of the inhibition of the formation of reactive oxygen species and the stimulation of antioxidant molecules. Similar to our observations with angiogenic balance this effect was only observed in the RUPP groups following AICAR treatment, suggesting a dependence on the presence of placental-ischemia.…”
Section: Discussionsupporting
confidence: 76%
“…Previous work has shown that oxidative stress plays an important role in preeclampsia and RUPP hypertension (25,31), and our present observations suggest that the effects of AICAR may be mediated by a combination of the inhibition of the formation of reactive oxygen species and the stimulation of antioxidant molecules. Similar to our observations with angiogenic balance this effect was only observed in the RUPP groups following AICAR treatment, suggesting a dependence on the presence of placental-ischemia.…”
Section: Discussionsupporting
confidence: 76%
“…Placental oxidative stress has been shown to be increased in preeclamptic women, and placental and renal oxidative stress is observed in preclinical models preeclampsia, and it is implicated in contributing to the development of vascular dysfunction, proteinuria, and hypertension during pregnancy (9,13,27,28). Importantly reactive oxygen species (ROS) is a byproduct of inflammation and is elevated in response to RUPP CD4ϩ T cells and IL-17-and AT 1 -AA-induced hypertension during pregnancy.…”
Section: Np T Reg Cell Supplementation Normalizes Tgf-␤ In Rupp Ratsmentioning
confidence: 99%
“…13 Three-month-old female Sprague Dawley rats were used. On day 14 of pregnancy, dams were randomly assigned to receive either a Sham (n=17) or RUPP (n=20) surgical procedure (see Methods in the online-only Data Supplement).…”
Section: Reduced Uteroplacental Perfusion Pressure In the Ratmentioning
confidence: 99%